Total Metabolit Sekunder dan Uji Aktivitas Antioksidan Daun Juwet (Syzygium cumini L.) dengan Spektrofotometer Uv-Vis: Total Secondary Metabolites and Test of Antioxidant Activity of Juwet Leaves (Syzygium cumini L.) with Uv-Vis Spectrophotometer - Tien, Tien Wahyu Handayani; Rasmiyanti, Ni Kadek Evy; Tandi, Joni; Magfirah (KOVALEN: Jurnal Riset Kimia, 2023)
The aim of this research is to determine the total amount of secondary metabolites (alkaloids, flavonoids, saponins and tannins) contained in the ethanol juice of juwet leaves (Syzygium cumini L.) using the UV-Vis spectrophotometry method and to determine the antioxidant activity of the ethanol juice of juwet leaves based on IC50 value. Determination of total levels of secondary metabolites using UV-Vis spectrophotometry and antioxidant testing using the DPPH method. The results of qualitative analysis of the ethanol juice of juwet leaves contained secondary metabolite compounds, namely flavonoids, saponins, tannins and alkaloids. The average value obtained for the level of total secondary metabolites for flavonoid compounds was 0.417% w/w., saponins 0.766 w/w., tannins 0.282 w/w and alkaloids 0.384% w/w. The results of testing the antioxidant activity of juwet leaf ethanol extract and quercetin as a comparison had antioxidant activity, the average IC50 results were 14.289 Â± 0.255 ppm and 102.45 ppm, therefore they were classified as moderate antioxidants.